2023
DOI: 10.3390/cancers15225460
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge about the Peritumoral Microenvironment in Glioblastoma

Gianluca Trevisi,
Annunziato Mangiola

Abstract: Glioblastoma is a deadly disease, with a mean overall survival of less than 2 years from diagnosis. Recurrence after gross total surgical resection and adjuvant chemo-radiotherapy almost invariably occurs within the so-called peritumoral brain zone (PBZ). The aim of this narrative review is to summarize the most relevant findings about the biological characteristics of the PBZ currently available in the medical literature. The PBZ presents several peculiar biological characteristics. The cellular landscape of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 139 publications
0
2
0
Order By: Relevance
“…PBZ is more like a transitional zone with a precancerous microenvironment, which is the basis for glioblastoma progression and recurrence. The understanding of PBZ may be related to the development of more effective treatment methods to prevent the development and recurrence of glioblastoma [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…PBZ is more like a transitional zone with a precancerous microenvironment, which is the basis for glioblastoma progression and recurrence. The understanding of PBZ may be related to the development of more effective treatment methods to prevent the development and recurrence of glioblastoma [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple mechanisms are involved in the chemoresistance of GBM, that is, overexpression of drug efflux transporter pumps such as P-glycoprotein, cancer stem cells, augmented DNA repair mechanisms, and dysregulation of apoptosis; this is considered to be an important factor responsible for drug resistance in GBM [ 19 ]. These factors highly influence the remarkable changes in tumor cells that lead to chemoresistance, but recently, new evidence has shown that the tumor microenvironment also plays a key role in chemosensitivity [ 20 , 21 ]. In addition to tumor cells, tumor lesions also contain a variety of stromal cells, including inflammatory blood cells, which infiltrate tumors, and endothelial cells (EC), which form blood vessels [ 22 ].…”
Section: Introductionmentioning
confidence: 99%